Somali American female refugees discuss their attitudes toward homosexuality and the gay and lesbian community. Issue 5 (4th May 2018) - Hunt, Shanda L.; Connor, Jennifer J.; Ciesinski, Amanda; Abdi, Cawo; Robinson, Beatrice 'Bean' E.
Abstract: Minnesota is home to the largest population of Somalis in the USA – most arriving as refugees from the civil war in Somalia. As Somali Americans adjust to life in the USA, they are likely to undergo shifts in their belief systems – including changes in their attitudes toward gays and lesbians. We examined the attitudes of 29 Somali American women in the Minneapolis-St. Paul metropolitan area toward homosexuality via face-to-face, semi-structured interviews. Transcripts were translated, transcribed and analysed using an approach informed by grounded theory. Three major themes were identified: (1) Islamic prohibitions against homosexuality; (2) homosexuals exiled to a hidden community; and (3) community members exploring tolerance. Participants' attitudes toward homosexuality were heavily influenced by religious doctrines and cultural contexts. This is the first known study in the USA of Somali American attitudes toward gays and lesbians. As people mass migrate from nations with negative attitudes toward homosexuality to countries with more progressive attitudes toward varied sexual orientations, refugee attitudes about homosexuality will undergo change. Through research and education, we can better understand how to increase tolerance toward and opportunities for visibility among gay and lesbian refugees throughout the diaspora.